CRITERIA IN SELECTING ENGLISH TEXTBOOKS FOR SMK STUDENTS - Supadi Supadi (Universitas Indraprasta PGRI, Jakarta, Indonesia, 2011)
The teachers have to decide what textbooks to use for teaching learning process. The students spend much time using textbooks in classroom, so selecting an appropriate one is important. The teachers’ creativity is also needed to strengthen the materials. The selecting of textbook is very important, the textbook has improved gradually for years, the process of selecting an appropriate textbook is not easy for the teachers. The textbook plays an important role for the teachers and the students. There are considerations for teachers to decide the textbook.Keywords: textbook, consideration, materials